Metabolic syndrome components individually worsen the outcome of acute pancreatitis: a systematic review and meta-analysis - Dobszai, Dalma; Obeidat, Mahmoud; Szalai, Eszter Ágnes; Veres, Dániel Sándor; Havelda, Luca; Papp, Renáta; Choi, Alim; Budai, Bettina Csilla; Csajbók, Dominika; Hegyi, Péter; Szentesi, Andrea (Frontiers in Endocrinology, 2025)
IntroductionThe obesity epidemic has led to a rise in related health conditions, with metabolic syndrome (MS) affecting 25% of Western populations. In severe acute pancreatitis (AP), mortality can reach 50%. Previous studies have linked MS elements to increased complications and mortality in AP. This meta-analysis aims to identify potential risk factors and their synergistic effects on AP outcomes.MethodsWe systematically searched PubMed, Embase, and the Cochrane Library up to November 1, 2023, and included studies based on predefined criteria. We examined the impact of MS and its factors (obesity, hypertension, diabetes mellitus, and hypertriglyceridemia) on AP outcomes, calculating pooled odds ratios (OR) with 95% confidence intervals (CIs). The protocol was registered in PROSPERO under number CRD42023471092.ResultsOut of 15,904 records, 89 studies were analyzed. Overweight and obesity were significant risk factors for complications (local OR: 2.677, 95%CI: 1.421-5.044; systemic OR: 2.404, 95%CI: 1.481-3.901) and severe AP (BMI≥30 kg/m2, OR: 3.058, 95%CI: 1.369-6.829). High triglyceride levels were associated with ICU admission (OR: 2.546, 95%CI: 1.529-4.237) and severe AP (OR: 2.686, 95%CI: 1.205-5.989); hypertension increased mortality (OR: 2.135, 95%CI: 1.870-2.437), while diabetes increased the odds of ICU admission (OR: 1.645, 95%CI: 1.358-1.992) and severe AP (OR: 1.49, 95%CI: 1.09-2.03). We found a non-significant trend toward increased odds of severe AP among patients with MS (OR = 1.398, 95% CI: 0.918–2.129).ConclusionIndividual components of MS are risk factors for complications, severity, and mortality in AP. Lifestyle counseling, education, and treatment of patients with obesity is crucial.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CD42023471092.